On Approximating the Distribution of Quadratic Forms in Gamma Random Variables and Exponential Order Statistics - A. Akbar Mohsenipour; Serge B. Provost (Journal of Statistical Theory and Applications (JSTA), 2013)
This paper proposes a moment-based approximation to the distribution of quadratic forms in gamma random variables. Quadratic forms in order statistics from an exponential population are considered as well. Actually,several test statistics can be expressed in terms of the latter. The density approximants are expressible as the product of a gamma type distributed base density function and a polynomial adjustment. Several illustrative examples are provided.